Evaluation of different sources of minerals on growth performance and serum mineral profile of crossbred pigs - Sonowal, Mridushmita; Nath, M; Kalita, K; Ahmed, H F (Indian Journal of Animal Production and Management, 2018)
Eighteen crossbred (Hampshire x Local) growing pigs of 3 months of age attaining about 19-20 kg body weight were randomly divided into 3 treatment groups of 6 pigs each and were replicated twice. The pigs under the different treatment groups were offered ad libitum standard grower ration supplemented with three different forms of mineral mixtures i.e. inorganic @ 1.5 Kg, T1; organic @ 100 g T2; and chelated inorganic @ 250 g per 100 Kg of the ration T3 for 90 days. Weight gain, feed intake and feed conversion ratio were 42.5± 0.71, 47.17± 0.30 and 41.00± 0.93 kg; 169.44± 3.04, 162.29± 3.00 and 167.02± 3.45 kg; 3.99± 0.08, and 3.44± 0.06 and 4.07± 0.04 for T1, T2 and T3 groups respectively. The serum mineral level showed no significant difference regarding calcium (Ca) and iron (Fe) among different treatment groups at 4.5 months of age. But the serum copper (Cu) and zinc (Zn) level were significantly higher (P<0.05) in the group which was fed with organic source of mineral than other two groups.